Wpływ akcesji Polski do UE na polski handel z Federacją Rosyjską - Kisiel-Łowczyc, Anna (Influence of Polish Accession to the European Union on Polish Trade with Russian Federation, 2005)
EU enlargement will generally affect on trade relations with the third countries; in especially evident way on trade relations the new member countries with the Rest of the World. The idea of this paper is to point out implications for Polish - Russian trade after Poland's accession to the EU. Analysis is based on the flows of Poland's import of goods from Russian Federation in y.2002, current Polish tariffs and EU external tariff (EU common trade policy and common external tariff come in force on l st of May, 2004). Highly concentrated Polish import from RF (ca 80% contain oil and gas) determine short term affects (custom - price competition). It also should underline effects of introduction the EU GSP (different from Polish one). With high probability other non-tariff trade policy measures (technical standards, antidumping procedures and environmental protection measures) could indirectly influence trade relations with RF.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 154-159